Financing Green Transitions: The Institutional Link in Sub-Saharan Africa’s Renewable Energy Drive - Okere, Wisdom; Ambe, Cosmas (International Journal of Energy Economics and Policy, 2025)
The transition to renewable energy in Sub-Saharan Africa is shaped by both financial and institutional determinants, yet empirical evidence on their joint effect remains limited. This study examines the relationship between financial resources and renewable energy adoption across 20 Sub-Saharan African nations from 2004 to 2023, using Fully Modified Ordinary Least Squares to capture long-run relationships and System Generalised Methods of Moments (GMM) to address endogeneity, it tests whether finance alone can drive RE growth and whether institutional quality moderates this effect. Results show that FDI is not sufficiently a driver for renewable energy transition, with effects varying across estimators. Also, political stability emerges as a driver for renewable energy adoption, while institutional quality has a mixed-moderating effect. These findings support recent evidence that governance quality and green finance mechanisms enhance the FDI flows for clean energy transition. This study contributes to the renewable energy finance literature by offering one of the first SSA-wide empirical analyses integrating finance-institution interaction in a green economy. Policy implications highlight the need for coordinated strategies that combine FDI inflows, institutional reforms and innovative green finance tailored to country-specific contexts.